Dipeptide of ψ-GSH Inhibits Oxidative Stress and Neuroinflammation in an Alzheimer's Disease Mouse Model - Abbas Raza; Wei Xie; Kwan-Hyun Kim; Venkateshwara Rao Dronamraju; Jessica Williams; Robert Vince; Swati S. More (MDPI AG, 2022)
Supplementation of glutathione (GSH) levels through varying formulations or precursors has thus far appeared to be a tenable strategy to ameliorate disease-associated oxidative stress. Metabolic liability of GSH and its precursors, i.e., hydrolysis by the ubiquitous γ-glutamyl transpeptidase (γ-GT), has limited successful clinical translation due to poor bioavailability. We addressed this problem through the design of γ-GT-resistant GSH analogue, ψ-GSH, which successfully substituted in GSH-dependent enzymatic systems and also offered promise as a therapeutic for Alzheimer's disease (AD). With the aim to improve its bioavailability, we studied the utility of a ψ-GSH precursor, dipeptide 2, as a potential AD therapeutic. Compound 2 retains the γ-GT stable ureide linkage and the thiol group for antioxidant property. By engaging glutathione synthetase, compound 2 was able to generate ψ-GSH in vivo. It was found to be a modest cofactor of glutathione peroxidase and prevented cytotoxicity of Aβ1-42-aggregates in vitro. Studies of compound 2 in an acute AD model generated by intracerebroventricular injection of Aβ1-42 showed cognitive benefits, which were augmented by its combination with glycine along with mitigation of oxidative stress and inflammatory pathology. Collectively, these results support further optimization and evaluation of ψ-GSH dipeptide as a potential therapeutic in transgenic AD models.